Development of Waste Management Application using GIS - Ardianti, Mifta; Suakanto, Sinung; Zulkarnaen, Rizky Zaki (Sistemasi: Jurnal Sistem Informasi, 2025)
Waste management is a serious challenge in modern society due to rapid population growth and urbanization. The inefficiency of conventional systems such as limited coordination, infrastructure, and reporting calls for a technology-based approach. This study develops a web-based waste management application integrated with Geographic Information System (GIS) to improve waste collection, monitoring, and reporting. The development method used is prototyping, allowing iterative improvement based on user feedback. The application includes key features such as waste bin location data entry, interactive map visualization with Leaflet.js, and transaction reporting. The result showed that the app is able to provide real-time visualization of waste bin locations, display waste statistics, and improve the transparency and efficiency of waste management operations. This research contributes to the development of environmental information systems that support data-driven decision-making and environmental conservation.